(untitled) (Studia Prawnicze / The Legal Studies, 2002)
Autor artykułu opisuje zagadnienia związane z naprawieniem szkody za dokonane przestępstwo w kontekście prawa karnego. Przedstawia dwie koncepcje idei sprawiedliwej odpłaty, pierwszą, która polega na tym, że państwo wymierza karę i oddziałuje za jej pomocą, drugą, której istota sprowadza się do potrzeby naprawy szkód wyrządzonych przez przestępstwo zarówno dla ofiary przestępstwa jak i całej wspólnoty. Autor powołując się na wybitnych niemieckich teoretyków prawa przedstawia regulacje prawne w tej materii obowiązujące w Niemczech oraz na poglądy doktryny niemieckiej dotyczące idei kompensacji w prawie karnym. The author of this article describes the issues related to damage reparation for a crime committed in the context of criminal law. He presents two concepts of the idea of just retribution, the first of which involves the state administering punishment and interacting through it, the second, the essence of which can be reduced to the need to repair the damage caused by crime to both the victim of the crime and the community as a whole. The author, citing prominent German legal theorists, presents the legal regulations applicable to these issues in force in Germany and the views of German doctrine regarding the idea of compensation in criminal law.